Le gouvernement économique de la filière sucre-énergie : blocages sectoriels et territoriaux des perspectives de développement au Brésil - Mathieu Fruleux (Revue de la Régulation)
This work analyzes the weight of agribusiness as an explanatory variable of the unsustainable character of the distributive inflexion of Brazil’s growth regime. It specifies its importance in the mode of regulation by the one it recovers in what we call an economic government of the actors’ game. This concept defines the set of arrangements seeking to modify the features of economic actors, their interaction and their relations to the authorities according to objectives which refer to a given governmental intentionality. It is showed that is established in this way a governance of the agribusiness’ actors which ensures the reproduction of its power in some sectoral and territorial regulations. The study of this governance links its institutional and organizational action to the one of the governmentality by characterizing the role of beliefs and theoretical models established in theoretical references of public policies. This analysis is structured in three parts. A first one revises the literature on the limits to growth simultaneously as it characterizes its influence as reference of the economic policy. A second part develops a case study of the sugar-energy chain, one of the leadings of agribusiness. This one uncovers the chain’s organizational and institutional changes and the uncertainties that induced its new governance. We conclude that the distributive intentionality of the economic government of the Workers’ Party did not give rise to a corresponding governance of actors of a re-industrialization conversely to the objective of growth of primary exports.